The secret life of a sea turtle - Bearzi, Maddalena (Roaring Brook Press, 2025)
"Follow the exciting and sometimes perilous life of a sea turtle in this robust nonfiction tale by sea turtle expert Maddalena Bearzi and illustrated by Alex Boersma"--